Assessing micromobility safety on horizontal curves of bike lanes: a video motion analysis methodology - Morteza Hossein Sabbaghian; David Llopis-Castelló; Alfredo García (Traffic Safety Research, 2024)
This study introduces a novel surrogate safety indicator, the ‘effective radius’, and a dynamic tracking methodology for assessing the safety of micromobility (MM) users on isolated bike lane curves, with a focus on geometric characteristics. The methodology involves six main pillars, including site selection, geometric data collection, video recording, speed and position extraction, visualization, and analysis. Naturalistic video data of bike lane users are captured to observe user behavior, and specific points along the curve centerline are identified for monitoring lateral position and speed on a selected curve site in Valencia, Spain. The analysis centers on a bidirectional bike lane featuring a sharp horizontal curve, incorporating the effective radius criteria to evaluate MM users' responses to geometry and environmental conditions. Findings reveal significant variation in effective radius, especially during left turns, primarily due to the geometry factor and the lane's positioning outside the curve. Lateral displacement heat maps indicate that left-turn users often have higher tendencies to violate dedicated lanes, posing collision risks. The speed analysis underscores potential conflicts and reduced handling capabilities for users breaching lane boundaries. The imperative need for well-informed design and safety measures in micromobility infrastructure is emphasized, considering the impact of geometric factors on user behavior and safety.